2020
DOI: 10.48550/arxiv.2007.04495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hack.VR: A Programming Game in Virtual Reality

Dominic Kao,
Christos Mousas,
Alejandra J. Magana
et al.

Abstract: Figure 1: Existing environments for programming in VR: A) Block-based programming (Cubely), B) Multiple-choice code snippet selection (Imikode), C) Block-based programming (VR-OCKS), D) World-building (NeosVR), E) Code visualization (Primitive), F) Visual programming (Glitchspace). All figures reproduced with permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Numerous studies have employed game-based approaches to enhance students' motivation and understanding in programming learning [2,3,9,11,12,29]. For instance, some studies have used a debugging game called Gidget to improve students' computational thinking and coding proficiency [11,12].…”
Section: Related Work 21 Gamified Approaches Towards Programming Lear...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have employed game-based approaches to enhance students' motivation and understanding in programming learning [2,3,9,11,12,29]. For instance, some studies have used a debugging game called Gidget to improve students' computational thinking and coding proficiency [11,12].…”
Section: Related Work 21 Gamified Approaches Towards Programming Lear...mentioning
confidence: 99%
“…Research indicates that incorporating game concepts into learning activities significantly improves students' understanding and motivation in programming [2,3,9,11,12,29] and electronics [5,6,14,26]. While some studies focus on these areas separately, the integration of robotics, electronics, embedded systems, and programming within a gamified framework remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The module was tested with the aid of 15 undergraduate students, and it was found that 92% of students found the system helped them learn OOP concepts. Consequently, Kao et al [41] developed a game called "HackVR" to also teach students OOP concepts. HackVR features nodes, which contain programming constructions such as objects, conditionals, function calls, and event handlers.…”
Section: B Virtual Reality For Computer Programming Educationmentioning
confidence: 99%